Pembrolizumab versus sintilimab in patients with advanced NSCLC: a retrospective multicenter study with propensity-score matching analysis - Xia, Zhengzheng; Hong, Juan; Yu, Xiangyang; Ran, Yuhua; Xie, Huali; Zhou, Ziyuan; Zuo, Jing; Chen, Tujia; Meng, Jun; Yang, Jun (Frontiers in Oncology, 2024)
BackgroundProgrammed cell death protein 1 (PD-1) inhibitors are commonly used worldwide for the management of non-small cell lung cancer (NSCLC). However, it remains unclear whether pembrolizumab and sintilimab, two of the most widely used PD-1 inhibitors in China, have significantly different effects on patients with NSCLC. A multicenter retrospective cohort study was designed and implemented using propensity-score matching (PSM) analysis to compare the effectiveness and safety profiles of pembrolizumab and sintilimab in patients with advanced NSCLC undergoing comprehensive therapy.MethodsA total of 225 patients who received comprehensive therapy including pembrolizumab (n = 127) or sintilimab (n = 98), from 1 January to 31 December 2020 and met the eligibility criteria were included. PSM analysis (1:1) was performed to balance potential baseline confounding factors. For both treatments, Kaplan–Meier analysis and Cox regression were used to compare 1-year progression-free survival (PFS), disease control rate (DCR), objective response rate (ORR), and rates of all adverse events (AEs).ResultsPSM analysis resulted in 63 matched pairs of patients. After PSM, the median PFS was 8.68 months in the sintilimab group and 9.46 months in the pembrolizumab group. The 1-year PFS showed no significant difference between the pembrolizumab and sintilimab groups before and after PSM (P = 0.873 and P = 0.574, respectively). Moreover, within the matched cohort, the pembrolizumab group had an ORR of 30.2% and a DCR of 84.1%, whereas the sintilimab group exhibited an ORR of 41.3% and a DCR of 88.9%. There were no significant differences in the ORR and DCR between the two groups (P = 0.248 and P = 0.629, respectively). The incidence of grade 3 or 4 treatment-related AEs was significantly higher in the pembrolizumab group than that in the sintilimab group (42.9% vs. 33.3%, P = 0.043). Multivariable Cox proportional hazards regression analysis indicated that the lines of treatment and regimens significantly influenced the PFS of patients (P <0.05).ConclusionsThis study demonstrated the similar effectiveness of sintilimab and pembrolizumab in the treatment of patients with advanced NSCLC, with sintilimab potentially displaying a superior clinical safety profile.Clinical trial registrationhttps://www.medicalresearch.org.cn/, identifier MR4423000113.